Contextual Approaches In Kaiwa Learning (Speaking) Japanese Language - Wuisang, J R R (Universitas Negeri Manado, 2019)
Speaking as one of the productive language skills and is an important activity in daily activities as meaningful interaction between humans is still not optimal in the Japanese language study program from an explanation before, this purpose of this study is to achieve the goal of speaking skills; the permitted curriculum in the Japanese Language Education study program, the development competency based curriculum in 2009 provides courses: Kaiwa 1 (ä¼šè©± ï¼‘) Conversation 1ã€ Kaiwa 2 (ä¼šè©± ï¼’) Conversation 2ã€ Kaiwa 3 (ä¼šè©± ï¼“) Conversation 3ã€ Kaiwa 4 (ä¼šè©± ï¼”) Conversation 4ã€ Kaiwa Enshuu ï¼ˆä¼šè©± æ¼”ç¿’ï¼‰ Conversation Deepening and one special course for Japanese speech skills, Nihongo Supiichi (æ—¥æœ¬èªž ã‚¹ ãƒ” ãƒ¼ ãƒ) Japanese Language Speech. In line with that idea, an important strategy in this learning is to teach students to be able to connect each concept with reality rather than emphasizing how much knowledge must be remembered and memorized. This research used CTL approaches which is contextual learning can be applied in any curriculum, any subject or field of study with a class regardless of the circumstances. In line with what was discussed by the Ministry of National Education, there are Seven (7) main principles that must be developed by teachers in the CTL approach. The contextual approach in Kaiwa learning is also expected to facilitate the achievement of learning goals, namely the aim of speaking Japanese skills to improve students' speaking abilities and provide many opportunities for the practice of talking with friends while making students actively involved in the learning process. Therefore, it is recommended that in Kaiwa learning (the name of the course for speaking skills in Japanese), I - IV this contextual approach can be used even maximized. The researcher realizes that this learning model is not the only one that is most suitable and relevant in teaching Japanese speaking skills courses but can be used as enrichment material.Keywords: Contextual Approaches; Kaiwa Learning; Speaking; Japanese Language.